The Transient Multidrug Resistance Phenotype of Salmonella enterica Swarming Cells Is Abolished by Sub-inhibitory Concentrations of Antimicrobial Compounds - Irazoki, Oihane; Campoy, Susana; Barbé, Jordi (Frontiers in Microbiology, 2017)
Swarming motility is the rapid and coordinated multicellular migration of bacteria across a moist surface. During swarming, bacterial cells exhibit increased resistance to multiple antibiotics, a phenomenon described as adaptive or transient resistance. In this study, we demonstrate that sub-inhibitory concentrations of cefotaxime, ciprofloxacin, trimethoprim, or chloramphenicol, but not that of amikacin, colistin, kanamycin or tetracycline, impair Salmonella enterica swarming. Chloramphenicol-treated S. enterica cells exhibited a clear decrease in their flagellar content, while treatment with other antibiotics that reduced swarming (cefotaxime, ciprofloxacin, and trimethoprim) inhibited polar chemoreceptor array assembly. Moreover, the increased resistance phenotype acquired by swarming cells was abolished by the presence of these antimicrobials. The same occurred in cells treated with these antimicrobial agents in combination with others that had no effect on swarming motility. Our results reveal the potential of inhibiting swarming abilities to enhance the therapeutic effectiveness of antimicrobial agents.